Intracerebroventricular Application of Dexmedetomidine Produces Antinociception and Does not Cause Neurotoxicity in Rats - Ersin Köksal; Deniz Karakaya; Bilge Can; Ayhan Bozkurt; Sibel Barış; Süleyman Sırrı Bilge; Yasemin Burcu Üstün (Balkan Medical Journal, 2013)
Background: Alpha2 agonists contribute to pain control at the level of the medulla spinalis. Alpha2 agonists are generally added to local anaesthetics to prolong spinal or epidural anaesthesia time.